Planting Steel into Concrete: Scientific Methods and Practical Experiences (Salam International Academic Journal, 2023)
This article presents the outcomes of research focused on the proper reinforcement of steel embedded in concrete elements of a building, including foundations, columns, and piers. The objective of this study is to provide a scientific and practical understanding of the results obtained from this process. Embedding reinforcing steel in concrete presents a significant challenge in Kabul city, emphasizing the need for a viable solution. Notably, there have been instances where municipal officials mistakenly severed overlapping steel connections in buildings, even after they had been correctly placed. Consequently, this article proposes a scientifically grounded approach to address this issue.Three different solutions for embedding reinforcing steel into concrete are introduced; each of these methods could be adaptable based on engineer recommendations or available resources. Each of these methods possesses unique characteristics, and this research offers a comprehensive exploration of these approaches, both from a theoretical and practical perspective.Our approach to achieving our research goal involves a thorough review of prior works, laboratory testing, compliance with established building codes, and on-site field testing. Laboratory results confirm that the process of embedding reinforcing steel into hardened concrete demonstrates strong resistance and complies with all technical requirements.In conclusion, among the three proposed methods, one stands out as the most promising. The article concludes by presenting recommendations aimed at further enhancing this research and urges engineers to give due consideration to these suggestions when embedding reinforcing steel into concrete. It is our hope that this research will yield positive outcomes for our construction engineers and contribute to the improvement of the process of embedding reinforcing steel into concrete.
Keywords: embedding reinforcing steel; epoxy adhesive; mechanical connection; mechanical anchor